2021
DOI: 10.15561/20755279.2021.0103
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the universities closure on physical activity and academic performance in physical education in university students during the COVID-19 pandemic

Abstract: Background and Study Aim. Physical activity (PA) is regarded as a critical component of a healthy lifestyle and disease prevention. Different constraints placed upon social interaction and public spaces due to COVID-19 could decrease PA and academic performance in physical education (PE) in student population. The purpose of the research was to assess overall and sport/fitness PA level and academic performance in PE in a sample of university students pre- to post-cancellation of face-to-face PE classes due to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 30 publications
1
13
0
1
Order By: Relevance
“…Physical Activity Research has shown that physical activity could protect against anxiety, especially during the pandemic (Deng et al, 2020;Osipov et al, 2021;Wathelet et al, 2020;Xiang et al, 2020). For instance, Xiang et al (2020) indicated that a significant association exists between high level of physical activity, specifically, stretching and resistance training, and low anxiety level.…”
Section: Social Interactionsmentioning
confidence: 99%
“…Physical Activity Research has shown that physical activity could protect against anxiety, especially during the pandemic (Deng et al, 2020;Osipov et al, 2021;Wathelet et al, 2020;Xiang et al, 2020). For instance, Xiang et al (2020) indicated that a significant association exists between high level of physical activity, specifically, stretching and resistance training, and low anxiety level.…”
Section: Social Interactionsmentioning
confidence: 99%
“…For the first time at the Department of Physical Culture, electronic courses have been developed and implemented for full-time students in the discipline of applied nature -"Applied Physical Education and Sports". The experience of our colleagues is expressed in a number of papers [24].…”
Section: Discussionmentioning
confidence: 99%
“…Some of the measures taken to curb COVID-19 were home quarantine, social distancing, and the closure of clubs and universities. Many students were taking virtual classes for the first time and had not experienced such an epidemic; this led to significant fear and stress (3). Medical and dental students, in particular, experienced significant stress during the corona due to academic stress, exposure to infection and contamination, networking, and lack of sleep, which affected their mental health (4).…”
Section: Dear Editormentioning
confidence: 99%